2000
DOI: 10.1603/0022-0493-93.6.1768
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Tebufenozide in Resistant and Susceptible Strains of Obliquebanded Leafroller (Lepidoptera: Tortricidae) and Resistance to New Insecticides

Abstract: Cross-resistance of the obliquebanded leafroller, Choristoneura rosaceana (Harris), to tebufenozide was reported from laboratory studies before it had been used in commercial orchards in New York State. Bioassays with obliquebanded leafroller larvae from tebufenozide and organophosphate susceptible and resistant colonies were conducted with chlorfenapyr, emamectin benzoate, fenoxycarb, fipronil, spinosad, and tebufenozide to determine if cross-resistance was present before these new insecticides were introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…In the same vein, it can be noted that increased resistance against dibenzoylhydrazine analogs in insect larvae always is accompanied by cross-resistance against other insecticides that have a different mode of action (Wearing, 1998;Waldstein and Reissig, 2000;Smirle et al, 2002;Smagghe et al, 2001;Moulton et al, 2002;Gore and Adamczyk, 2004;Cao and Han, 2006). These findings indicate at increased metabolism or decreased penetration/absorption as the main mechanism of resistance in larvae.…”
Section: Discussionmentioning
confidence: 98%
“…In the same vein, it can be noted that increased resistance against dibenzoylhydrazine analogs in insect larvae always is accompanied by cross-resistance against other insecticides that have a different mode of action (Wearing, 1998;Waldstein and Reissig, 2000;Smirle et al, 2002;Smagghe et al, 2001;Moulton et al, 2002;Gore and Adamczyk, 2004;Cao and Han, 2006). These findings indicate at increased metabolism or decreased penetration/absorption as the main mechanism of resistance in larvae.…”
Section: Discussionmentioning
confidence: 98%
“…Nakagawa et al (1995) also reported that most dibenzoylhydrazines are only marginally synergized in vivo with metabolic inhibitors (PBO and DEF), while no synergistic effect was observed in the cultured integument in vitro system. On the other hand, in the in vivo system of a whole insect body, previous studies (Smagghe et al, 1998(Smagghe et al, , 2003Waldstein and Reissig, 2000;Smagghe, 2004) indicated oxidative and glutathione-S-transferase metabolism as the primary reason for development of resistance to tebufenozide and methoxyfenozide. In addition, amidase-mediated metabolism may occur for the dibenzoylhydrazines because of the presence of an amide bond in the structure of these compounds (Waldstein and Reissig, 2000;Smagghe, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the in vivo system of a whole insect body, previous studies (Smagghe et al, 1998(Smagghe et al, , 2003Waldstein and Reissig, 2000;Smagghe, 2004) indicated oxidative and glutathione-S-transferase metabolism as the primary reason for development of resistance to tebufenozide and methoxyfenozide. In addition, amidase-mediated metabolism may occur for the dibenzoylhydrazines because of the presence of an amide bond in the structure of these compounds (Waldstein and Reissig, 2000;Smagghe, 2004). Sundaram et al (1998) demonstrated that active exclusion of tebufenozide accounted for resistance in dipteran Drosophila cells (DM-2 and Kc) compared to lepidopteran cells .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Þnding that leafrollers can be resistant to materials previously not used in orchards (Waldstein and Reissig 2000, Ahmad et al 2002, Smirle et al 2002 has demonstrated the necessity of baseline testing of leafroller populations before new control materials are introduced into pest management systems.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticide resistance in populations of C. rosaceana has also been reported from several apple-producing regions of eastern North America (Reissig et al 1986, Carriè re et al 1996, Pree et al 2001, including resistance to the recently introduced insect growth regulator (IGR) tebufenozide (Waldstein et al 1999). In populations of C. rosaceana from New York State, Waldstein and Reissig (2000) reported resistance to several materials with novel modes of action, even if they had not been used previously in the orchards where the insects had been obtained. Smirle et al (2002) documented signiÞcant levels of resistance to indoxacarb (Avaunt, DuPont, Wilmington, DE) in populations of C. rosaceana from British Columbia.…”
mentioning
confidence: 93%